How Well Can Architecture Students Comprehend the Site as Design Context without Performing On-site Observation? - Aldyfra Luhulima Lukman; Sahid Sahid (International Journal of Built Environment and Scientific Research, 2021)
The Covid-19 pandemic has forced daily activities, including educational activities, to prevent or minimize the transmission or spread of the disease caused by a coronavirus. Online architecture education demands significant adjustments in the embedded learning methods, especially those that entail architecture design studio. An architecture design studio that commonly involves direct interaction in physical spaces should be performed through online media and computer screens. Architecture students' comprehension of site or design contexts is usually formed by collecting information through on-site observation.  In an online architecture design studio, an on-site survey is replaced by observing visual representation of the site. This study aims to identify how well architecture students in architecture design studios can comprehend the site when they have to rely on data acquired from virtual observation and/or on secondary data and how beneficial the comprehension to their design process is. Students' understanding of the site was measured with thirteen attributes of the site. It can be concluded that when architecture students depend on mere audio and/or visual data collected from the internet and/or other people, without visiting the site, they tend to have partial comprehension regarding the site as context. Contextual and responsive design demands a comprehensive understanding of all attributes of the site. The architecture design studio should incorporate on-site observation concerning the site according to the health protocol, so that the architecture students involved in the studio can have a better understanding of the site and create more contextual and responsive designs